Intrapreneurship as leverage for new job - Costa, Massimiliano; Strano, Andrea (Formazione & insegnamento, 2017)
Nowadays work transforms its meaning and its representation. The concept of competence is changing: it’s referred to the ability to act, rather than to performance. Workers that are truly qualified and competent, also possess entrepreneurial skills, since they act on opportunities and ideas to transform them into value for themselves and for the others. The research disclosed in this article had studied entrepreneurial competence through the Capability Approach, involving more than one hundred people. Results shows how the real meaning of entrepreneurial competence focuses on the importance of being able to choose, as key figure of personal capability, supporting in this way workers’ human development and fulfilment.